(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The article examines the content and nature of the acceleration of environmental globalization processes in the world on the eve of the new century, the direction of its impact on the environment, in particular, the reasons for the shortage of fresh water and proposals for its elimination. Also, problems that have a serious impact on the ecological environment of Uzbekistan, factors that change the ecological situation, improving relations and usugublyayushchie problems are also analyzed in detail.